Daily Ischemic Preconditioning Provides Sustained Protection From Ischemia–Reperfusion Induced Endothelial Dysfunction: A Human Study. Issue 1 (22nd February 2013) - Luca, Mary Clare; Liuni, Andrew; McLaughlin, Kelsey; Gori, Tommaso; Parker, John D.
Abstract : Background: It is well established that acute ischemic preconditioning (IPC) protects against ischemia–reperfusion (IR) injury; however, the effectiveness of repeated IPC exposure has not been extensively investigated. We aimed to determine whether daily IPC episodes provide continued protection from IR injury in a human forearm model, and the role of cyclooxygenase‐2 in these responses. Methods and Results: Thirty healthy volunteers were randomized to participate in 2 of 3 protocols (IR alone, 1‐day IPC, 7‐day IPC) in an operator‐blinded, crossover design. Subjects in the IR alone protocol underwent flow‐mediated dilation (FMD) measurements pre‐ and post‐IR (15′ upper‐arm ischemia and 15′ reperfusion). The 1‐day IPC protocol involved FMD measurements before and after 1 episode of IPC (3 cycles of 5′ upper‐arm ischemia and 5′ reperfusion) and IR. Day 7 of the 7‐day IPC protocol was identical to the 1‐day IPC protocol but was preceded by single daily episodes of IPC for 6 days prior. During each protocol, subjects received a 7‐day treatment of either the cyclooxygenase‐2 inhibitor celecoxib or placebo. Pre‐IR FMD was similar between groups. IR alone reduced FMD post‐IR (placebo, ΔFMD: −4.4±0.7%; celecoxib, ΔFMD: −5.0±0.5%). One‐day IPC completely prevented this effect (placebo, ΔFMD: −1.1±0.6%; celecoxib, ΔFMD: 0.0±0.7%; P <0.0001). Similarly, 7‐day IPC demonstrated persistent endothelial protection post‐IR (placebo, ΔFMD: −0.9±0.9%; celecoxib, ΔFMD: 0.0±0.8%; P <0.0001, P <0.0001 for ANOVA effect of IPC protocol). Celecoxib did not alter responses to IR in any protocol. Conclusions: Daily episodes of IPC provide sustained protection from IR‐induced endothelial dysfunction in humans through a mechanism that appears cyclooxygenase‐2‐independent.